Insights on the biological role of ultrafine particles of size PM<0.25: A prospective study from New Delhi. (1st January 2021) - Das, Ananya; Kumar, Arun; Habib, Gazala; Vivekanandan, Perumal
Abstract: When the total ambient PM2.5 levels are several-fold higher than the recommended limit, it may be important to study the distributions of different sizes of particulate matter (PM). Here, we assess the distributions of various sizes of total PM2.5 for 12 months (on a monthly basis) in New Delhi, India. Importantly, we found that ultrafine particles (i.e., particles <0.5 μm) contribute significantly to total PM2.5 . PM<0.25 were the most cytotoxic particles to human lung epithelial cells in all the 12 months. In addition, PM<0.25 were associated with significantly higher cytotoxicity per unit mass compared to other size fractions constituting PM2.5 . For any given size of PM, the amount of reactive oxygen species (ROS) generated per unit mass is higher for the month of March as compared to that for the rest of the months in the year. The higher ROS generations for all sizes of PM collected in the month of March was not explained by differences in their metal content values. Our data suggests the lack of correlation between total PM2.5 levels and the highly cytotoxic PM<0.25 . In summary, this work establishes the need for policy changes to routinely monitor PM<0.25 and the necessity to establish exposure limits for PM<0.25, especially when the total PM2.5 levels are breached. Graphical abstract: Image 1 Highlights: Increased cytotoxicity of PM<0.25 per unit mass as compared to other size fractions constituting PM2.5 . Total PM2.5 levels do not have any correlation with PM<0.25 levels highlighting the need to establish exposure limits for PM<0.25 levels. The need to start monitoring of ultrafine particles (i.e. PM<0.25, PM0.5, PM1.0 ) in countries with elevated PM2.5 levels, especially when the total PM2.5 levels breaches the limit by several folds. Abstract : Main findings: (a) Increased cytotoxicity of PM<0.25 (b) the lack of correlation between PM2.5 levels and PM<0.25 levels (c) the need to start monitoring ultrafine particles (i.e., PM<0.25 ) in countries with elevated PM2.5 levels.